Literasi Soft Skills untuk Mendukung Ekstrakurikuler Berbasis Keterampilan Vokasi pada Peserta Didik di Pendidikan Kasih Anak Bangsa - Nopita (Jurusan Ilmu Pendidikan - Universitas Lampung, 2024)
The soft and hard skills literacy based training program is considered necessary, especially for non-secular based educational units, such as theological schools, to equip students with skills so that after graduation they are able to become independent mission workers. The implementation of this service program activity is divided into three sessions, namely interactive lectures, demonstrations and training, and practice / demonstrations. Observation and qualitative assessment were conducted in each session. The results of the program show that students understand and are able to practice the spiritual and professional principles of talent, soft and hard skills.